2024
DOI: 10.1037/tra0001351
|View full text |Cite
|
Sign up to set email alerts
|

Más que palabras: Understanding the mental health and behavioral consequences of sociodemographic risk and deportation fears in Latinx families.

Abstract: This document is copyrighted by the American Psychological Association or one of its allied publishers.This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.examined its association with mental health in this community. We found that observed maternal deportation fears are linked with greater depression for both youth and mothers. However, these associations are only present when the family's exposure to demographic stress is lower. Providers working … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…Arreola et al (2024) take an innovative approach to understanding intergenerational transmission of mental illness among migrant mothers and their youth aged 11–17, using Linguistic Inquiry and Word Count. Focusing on the language that mothers use to describe their fears of deportation, they discovered associations of these words to mothers’ depression and to youth depression rates as well.…”
Section: Symptomsmentioning
confidence: 99%
“…Arreola et al (2024) take an innovative approach to understanding intergenerational transmission of mental illness among migrant mothers and their youth aged 11–17, using Linguistic Inquiry and Word Count. Focusing on the language that mothers use to describe their fears of deportation, they discovered associations of these words to mothers’ depression and to youth depression rates as well.…”
Section: Symptomsmentioning
confidence: 99%
“…Some of these negative outcomes may be attributable to unique stressors among this population, such as immigration political rhetoric fueling deportation fears. Research has shown that deportation fears increase the risk for depression in both youth and parents of Latinx families [5]. In addition to unique minority stress influences, prior research suggests disparities in service utilization as an explanation for poorer mental health outcomes among Latinx youth.…”
Section: Introductionmentioning
confidence: 99%